Have wolves (Canis lupus) finally scared moose (Alces alces) in Sweden? - Jamieson, Mark (SLU/Dept. of Ecology, 2018)
Carnivores are coming back to Europe and the repercussions of their return on prey species is not fully understood. Research from North American studies suggests predators can indirectly affect how ungulates will select their habitat which can result in a change in vegetation growth as browsing pressure is relaxed in risky areas. The highly human dominated landscapes of European countries could limit the effect predators have, as humans alter so much of the environment, from forestry to hunting. I use resource selection functions to analyse 20 years of data collected in the Grimsö Wildlife Research Area (140 km2), in a before/after study design to see if the return of the wolf (Canis lupus) in Scandinavia has caused moose (Alces alces) to change how they select winter habitat. I show a change in moose habitat selection after wolf recolonization, but find no conclusive evidence of an indirect effect of wolves. A more likely explanation for the observed changes in moose habitat selection within the Grimsö Wildlife Research Area is a functional response between moose and forage availability.